Analyze and build a sales plan for the Suncatcher product line on the Amazon e-commerce platform at Danazon Company Limited - Mai, Thi Loc (Vietnam-Korea University of Information and Communication Technology, 2024)
Bachelor thesis of Business Administration - E-commerce Management